Case report: Incidental MALT lymphoma of the left adrenal gland mimicking a metastatic spread within durvalumab maintenance treatment in inoperable stage III non-small cell lung cancer - Käsmann, Lukas; Degerli, Esra; El-Marouk, Karim; Manapov, Farkhad (Frontiers in Oncology, 2024)
Durvalumab after chemotherapy in non-operable stage III non-small cell lung cancer (NSCLC) is the standard of care worldwide. We present a patient with the incidental discovery of a unilateral MALT lymphoma of the adrenal gland and adrenalitis during durvalumab maintenance treatment detected by 18F-FDG-PET/CT. We assessed the clinical and histopathological findings, radiological examinations and overall treatment. Our work emphasizes the significance of considering other differential diagnoses and the importance of multidisciplinary treatment of the findings, especially within clinical trials.